Factores asociados a neoplasia cervical en mujeres en edad fértil en el Centro Materno Perinatal-Tarapoto. Enero 1998 - Diciembre 2000 - Zelada Mori, Ymelda (2002)
This paper is an analytical cross-sectional study, case-control, retrospective, drawn in Maternal Perinatal Center - Tarapoto. January 1998 - December 2000; in which 35 cases of cervical neoplasia and / or cancer in women of childbearing age was found and 10 cases were dismissed for not being registered in the clinical records the main variables for elaboraci6n this investigation. We worked with 25 cases and 50 controls. The respective data were entered in Epi lnfo 6.04 for OC 95% statistical significance p <0.05). The incidence of cervical neoplasia found is 6.45 per 1000 women of childbearing age. The main associated factors were: Early initiation of sexual intercourse, multiple sexual partners, low education, gynecological history and the largest number of abortions. The present study identified factors associated with cervical neoplasia and / or cancer to suggest behaviors to reduce this public health problem that is affecting the female population of the San Martín Region.